The German and Hungarian identity management and nation building - Hermanik, Klaus-Jürgen (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2008)
This paper shed light upon the identity management of the Germans and Hungarians in Slavonia (CRO) and Vojvodina-area (SRB). It gives examples of the present ethnic groupsć societies. It gives further examples of the culture of remembrance (monuments, memorial-parks, ceremonies, etc.) and their specific role in Croatian - and Serbian nation-building processes since 1989/90. These topics are strongly connected with minority questions, too. Furthermore the paper will also give insights into the identity management coming from abroad, mainly from Germany, Austria or Switzerland for the German ethnic group and from Hungary for the Hungarian ethnic group. Finally, one tries to answer the question, whether the above mentioned commemorative activities lead to an establishment of a more positive relationship between the respective majority (Croats and Serbs) and the respective minority (Germans and Hungarians) groups.
Keywords: Balkan; Balkans; narodne manjšine; nemška manjšina; madžarska manjšina; narodna identiteta; kultura spominjanja; oblikovanje identitete